Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s11187-018-9988-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-employment effects on regional growth: a bigger bang for a buck?

Abstract: Economic development policies often revolve around supporting small businesses and new firm creation as they are locally grown and likely can be more influenced by state and local policy. Two prominent strands of current research-the regional economic growth and small business/entrepreneurship literatures-elucidate the importance of small, young firms for regional economic performance and the crucial role urban-rural proximity plays in the distribution of growth across space. Keeping these two research traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 62 publications
4
24
0
Order By: Relevance
“…Fritsch and Wyrwich (2017) study German regions, finding a significant long-run effect of start-up activity on job growth. Other recent studies find similar results (Tsvetkova et al, 2019;Lee (2017). Tsvetkova et al (2019) compare the local employment effects from exogenous net changes in self-employment with similar changes in regular wage employment in US counties.…”
Section: The Importance Of the Local Rate Of New Firm Formationsupporting
confidence: 80%
See 1 more Smart Citation
“…Fritsch and Wyrwich (2017) study German regions, finding a significant long-run effect of start-up activity on job growth. Other recent studies find similar results (Tsvetkova et al, 2019;Lee (2017). Tsvetkova et al (2019) compare the local employment effects from exogenous net changes in self-employment with similar changes in regular wage employment in US counties.…”
Section: The Importance Of the Local Rate Of New Firm Formationsupporting
confidence: 80%
“…Various explanations have been put forth for why new and small firms are especially important for local economies including their propensity to buy inputs locally, their profits remain local, and it signals future growth opportunities in the local economy. Finally, Tsvetkova et al (2019) find that small and new business formation is linked to much larger local job and income multipliers than equivalent changes for existing businesses. Taken together, this motivates analyzing the drivers of the local rate of new firm formation.…”
Section: Introductionmentioning
confidence: 88%
“…Ayalew & Zeleke (2018) and Afolabi, Kareem, Okubanjo, Ogunbanjo, & Aninkan (2017) also found a similar effect. The study also found that the development of self -employment will significantly improve the standard of living and growth of the economy which aligned with findings from other reseraches Tsvetkova, Partridge, & Betz, 2016;Fields, 2014;Goetz & Rupasingha, 2013;Bashir, Gebremedhin, & Fletcher, 2011;Startienė & Remeikienė, 2013). However, Goetz, Fleming, & Rupasingha (2012) noted that self -employment may have little or no benefit for the local and national economy as it may just be a temporary measure for those laid off or job seekers till their condition improves.…”
Section: Hypothesis Testingsupporting
confidence: 77%
“…Somefun (2014) in his discourse submitted that self -employment must be given an imperative place if the nation must revitalise its economy and reduce the choking high rate of unemployment which is in agreement with the assertion of the youths and that of other studies (Ogunrinola, 2011). This implies that self -employment increases local, regional and national income, reduce unempliyment through job provision and improve the standard of living of the citizens by lifting them out of poverty (Tsvetkova, Partridge, & Betz, 2016;Fields, 2014;Goetz & Rupasingha, 2013;Bashir, Gebremedhin, & Fletcher, 2011) Table 4 shows that 86.3% of the youths agreed that lack of strong patent law is a challenge to self -employed development, high cost of doing business (88.9%), and lack of knowledge of entrepreneurship in the basic science and technology (72.9%). Also, other challenges to self -employment include lack of patronage of local products (92.7%), lack of conducive environment (77.5%) and lack of constant power supply (75.2%).…”
Section: Results Table 1: Demographic Characteristics Of the Respondentsmentioning
confidence: 90%
“…As the second step, we calculate average investmentcash flow sensitivity measures (β1 in Equation 7) for each functional region in Sweden (56 total) 10 . To derive regional values, we estimate Equation 7separately by region.…”
Section: Regional Estimatesmentioning
confidence: 99%